PENGARUH PENDEKATAN RME TERHADAP PEMAHAMAN KONSEP DAN KEMAMPUAN PEMECAHAN MASALAH SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI - Nurbaiti, Nurbaiti; Hartoyo, Agung; Astuti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis quasi experiment research aimed to know the effect of realistic mathematic education approach to student’s conceptual understanding and problem solving ability in linear inequality of one variable subject. There were two class as samples of this research, there were experiment class and control class. Experiment class had 37 students and control class had 38 students. Based on result of Independent Samples T Test, the signifficant score was 0,0000. The score showed that there was difference of average score between realistic mathematic education approach and conventional approach to student’s conceptual understanding and problem solving ability. So that the effect size’s score of conceptual underpstanding was 0,78 and categorized as medium. Then, the effect size’s score of problem solving ability was 0,73 and categorized as medium. Based on these result, we can conclude there was more positive effect to student’s conceptual understanding and problem solving ability using realistic mathematic education approach in linear inequality of one variable subject than conventional approach.Keyword :Realistic Mathematich Education, conceptual understanding, problem solvng.